THE SELF REGULATION ON PEER TO PEER (P2P) OF LENDING INDUSTRY IN INDONESIA AS PROBLEMS AND PROSPECTS - Mukti Fajar; Reni Budi Setianingrum (Jurnal Pembaharuan Hukum, 2022)
The purpose of this research is to find out that the industrial revolution 4.0 has had a significant impact, especially in the use of technology and the internet in daily human activities, both in personal life and in economic activities. This study used a normative legal research method that examines various legal theories related to financial technology both in Indonesia and other countries. The P2P lending service carries out business activities by providing, managing, and operating money-borrowing services by utilizing information technology as a liaison. Peer to Peer (P2P) Lending in Indonesia is regulated in POJK No. 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services. This regulation is the basis for the implementation of P2P Lending business activities or online borrowing, which is one type of fintech, including regulations regarding supervision carried out by the Financial Services Authority (OJK) on the implementation of these business activities. However, in practice, lending by P2P Fintech has attracted a lot of controversies because there are still many problems, including interest arrangements, the rise of illegal fintech applications and also the weakness of consumer protection where these things have not been fully addressed and regulated by POJK No. 77/POJK. 01/2016.